2020
DOI: 10.1007/s10560-019-00618-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Arrests: A Race Specific Model Explaining Arrest Rates Across Black and White Young Adults

Abstract: Three theories attempt to explain the racial disparities in arrest between White and Black Americans: Differential Involvement Hypothesis, Differential Selection and Processing Hypothesis, and Social Disorganization Theory. We tested these hypotheses simultaneously in a multiple-group longitudinal panel model with the ADD Health dataset (Black n = 2459, White n = 7403). After controlling for contextual and behavioral factors, we still found Black young adults were arrested seven times more often than their Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Of the new measures added, only the Black-White poverty ratio remains significant. This positive association is in line with previous studies suggesting greater structural disadvantages facing minorities partially explain racial inequalities in formal social control (Cureton 2000; Gase et al 2016; Kirk 2008; LaFree et al 2010; Parker et al 2005; Schleiden et al 2020). In sum, results presented in Table 2 demonstrate slavery is directly associated with racial disparities in arrests for violent offenses.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Of the new measures added, only the Black-White poverty ratio remains significant. This positive association is in line with previous studies suggesting greater structural disadvantages facing minorities partially explain racial inequalities in formal social control (Cureton 2000; Gase et al 2016; Kirk 2008; LaFree et al 2010; Parker et al 2005; Schleiden et al 2020). In sum, results presented in Table 2 demonstrate slavery is directly associated with racial disparities in arrests for violent offenses.…”
Section: Resultssupporting
confidence: 92%
“…Extant scholarship also points to racial disparities in educational and economic disadvantage as potential sources of racial disparities in arrest rates (LaFree et al 2010;Ousey and Lee 2008;Parker et al 2005). Criminological studies examining the role of concentrated minority disadvantage in generating racial disparities in arrest rates mention poverty specifically as an important manifestation of structural disadvantage (Kirk 2008;LaFree et al 2010;Parker et al 2005;Schleiden et al 2020). Legacy of slavery scholarship finds a positive association between slavery and Black-White disparities in poverty (Curtis and O'Connell 2017;O'Connell 2012O'Connell , 2020O'Connell et al 2020) and demonstrates slavery's negative consequences for Black educational outcomes (Bertocchi and Dimico 2012;Reece and O'Connell 2016).…”
Section: Concentrated Racial Disadvantagementioning
confidence: 99%
“…It is possible that children from high and low SES families and neighbourhoods engage in similar levels of criminal behaviour, but that those with low SES backgrounds are more likely to get caught and/or are more likely to be arrested. Some research has shown that police officers have substantial discretion, which leads to disparities in arrests based on demographic characteristics (Campbell et al, 2021; Gaston, 2019; Schleiden et al, 2020). Indeed, police officers are more likely to make arrests in low SES neighbourhoods than in high SES neighbourhoods (Lum, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the distribution of these experiences is not equal. Black adults are arrested at rates seven times that of their White counterparts (Schleiden et al, 2020), and arrests involving Black and Hispanic individuals are 50% more likely to involve the use of force (Fryer, 2019). While no two arrests or interactions with law enforcement are the same, what holds true is how this initial phase of justice involvement can lead to the removal of an individual from the community, and in the case of some fathers, from children's lives.…”
Section: Parental Arrestmentioning
confidence: 99%